P059 INDOLEAMINE 2, 3-DIOXYGENASE 1 EXPRESSION PROMOTES EPITHELIAL SECRETORY CELL DIFFERENTIATION VIA ARYL HYDROCARBON RECEPTOR. (18th January 2018) - Alvarado, David; Santhanam, Srikanth; Iticovici, Micah; Chen, Baosheng; Ciorba, Matthew
Abstract: Background: In mouse models of IBD, the tryptophan metabolizing enzyme indoleamine 2, 3-dioxygenase 1 (IDO1) has been shown to limit disease severity. Our studies indicate that intestinal epithelial cells are an important source of IDO1 expression in these conditions; however the mechanism remains unknown. We have identified IDO1 expression in goblet cells as well as colocalization with secreted mucin. As mucin is both a physical barrier against bacterial invasion and an energy substrate for luminal microbes, we hypothesized that epithelial IDO1 may limit colitis severity is through enhancement of mucus barrier function. Methods: We generated a novel transgenic mouse model which overexpresses EGFP-tagged IDO1 specifically in the intestinal epithelium (IDO1-TG). Primary epithelial spheroid cultures were utilized to assess growth and gene expression by RT-qPCR and immunofluorescence in vitro. Results: Histology revealed an increase in goblet and Paneth cells in IDO1-TG small intestine tissue. Analysis of gene expression in enteroids revealed higher levels of stem cell markers Lgr5 and Lrig1 in IDO1-TG compared to wildtype (WT). Additionally, the secretory lineage transcription factor Atoh1 and downstream effector Gfi1 were significantly upregulated in IDO1-TG, leading to enhanced secretory lineage markers for Paneth cells, goblet cells, and enteroendocrine cells, and a reduction in absorptive cell markers. Enteroids genetically deficient of Ido1 showed the opposite trend. Inhibition of IDO1 did not reduce expression of secretory cell markers, but incubation with a specific inhibitor of the aryl hydrocarbon receptor restored baseline expression levels. Conclusions: Taken together, these data indicate expression of IDO1 in the intestinal epithelium promotes secretory cell differentiation and mucus production, whereby identifying a novel mechanism by which non-enzymatic activity of IDO1 modulates intestinal homeostasis.